El Nino, Monsoon and its Effect on Agriculture in North-Eastern India - Saikia, U S; Goswami, B. (Indian Farming, 2015)
There is a strong linkage between El Nino, Monsoon and kharif season agriculture in the north-eastern region of India. El nino is defined by prolonged warming in the Pacific Ocean sea surface water temperatures as compared to the average value. The anomaly of this temperature diffierence occurs at irregular interals of 2-7 years and lasts for 9 months to two years. The possibility of an El Nino effect during 2014-15 has been predicted by the World Meterological Organizations.